How far mobile learning has gone through in tourism and hospitality education : A bibliometric analysis. - Salmalina, Salleh; Hui, Lee Shih; Damien, Mikeng (Universiti Teknologi MARA, 2024)
The advent of mobile learning within the educational system has created numerous opportunities in the field, which has led to extensive research publications. However, not much is known about the trend of mobile learning trend in the field of Tourism and Hospitality education. Hence, this research aims to provide a bibliometric overview of the educational publications pertaining to mobile learning in Tourism and Hospitality education indexed by WOS databases from the years 2013 to 2023. A total of 22 publications were retrieved and included in the bibliometric analysis. The results reveal a prevailing trend in mobile learning within the field of Tourism and Hospitality education, demonstrating that the number of publications increased significantly during the outbreak of the Covid-19 pandemic. A significant number of publications were found to be published from China and Taiwan. The present study also identified themes based on the keywords generated from the bibliometric analysis, which emphasised the potential of social media as a mobile learning platform in the context of Tourism and Hospitality education. The present findings set a foundation for future researchers and educationists to explore the use of mobile learning for different educational settings, curriculum designs, and target learners in the present context.